Women and Patriarchal Society in Three Stories of Pilar Dughi - Susti, Alejandro (2024)
The article examines three stories published by Peruvian writer Pilar Dughi (1956-2006) throughout her career as a storyteller: “Conciliación”, “Futuro prometido” and “Los guiños del destino”. The analysis and the interpretation address the representation of their female protagonists from a gender perspective, taking into account the roles, identities and positions that the patriarchal order assigns to them, both in the private and public spheres. The central thesis of the article is that the protagonists, through acceptance or negotiation in their relationships with the opposite sex —whether within or outside of marriage —, represent the complexity of “being a woman” in a society in which diverse and contradictory discourses on female gender identity coexist.